Analysis of Pneumocystis Transcription Factor Evolution and Implications for Biology and Lifestyle - Ryan Ames; Alistair J. P. Brown; Ivana Gudelj; Olga A. Nev (mBio, 2023)
ABSTRACT Pneumocystis jirovecii kills hundreds of thousands of immunocompromised patients each year. Yet many aspects of the biology of this obligate pathogen remain obscure because it is not possible to culture the fungus in vitro independently of its host. Consequently, our understanding of Pneumocystis pathobiology is heavily reliant upon bioinformatic inferences. We have exploited a powerful combination of genomic and phylogenetic approaches to examine the evolution of transcription factors in Pneumocystis species. We selected protein families (Pfam families) that correspond to transcriptional regulators and used bioinformatic approaches to compare these families in the seven Pneumocystis species that have been sequenced to date with those from other yeasts, other human and plant pathogens, and other obligate parasites. Some Pfam families of transcription factors have undergone significant reduction during their evolution in the Pneumocystis genus, and other Pfam families have been lost or appear to be in the process of being lost. Meanwhile, other transcription factor families have been retained in Pneumocystis species, and some even appear to have undergone expansion. On this basis, Pneumocystis species seem to have retained transcriptional regulators that control chromosome maintenance, ribosomal gene regulation, RNA processing and modification, and respiration. Meanwhile, regulators that promote the assimilation of alternative carbon sources, amino acid, lipid, and sterol biosynthesis, and iron sensing and homeostasis appear to have been lost. Our analyses of transcription factor retention, loss, and gain provide important insights into the biology and lifestyle of Pneumocystis. IMPORTANCE Pneumocystis jirovecii is a major fungal pathogen of humans that infects healthy individuals, colonizing the lungs of infants. In immunocompromised and transplant patients, this fungus causes life-threatening pneumonia, and these Pneumocystis infections remain among the most common and serious infections in HIV/AIDS patients. Yet we remain remarkably ignorant about the biology and epidemiology of Pneumocystis due to the inability to culture this fungus in vitro. Our analyses of transcription factor retentions, losses, and gains in sequenced Pneumocystis species provide valuable new views of their specialized biology, suggesting the retention of many metabolic and stress regulators and the loss of others that are essential in free-living fungi. Given the lack of in vitro culture methods for Pneumocystis, this powerful bioinformatic approach has advanced our understanding of the lifestyle of P. jirovecii and the nature of its dependence on the host for survival.